Evaluasi Manajemen Limbah Medis di Puskesmas Kabupaten Luwu - Afifah Idelma Makmur; Bayu Wahyudi; Yani Restiani Widjaja (ManBiz: Journal of Management and Business, 2025)
Medical waste is a hazardous by-product of healthcare activities that poses risks to human health and the environment, requiring proper management in accordance with regulations. This qualitative study evaluated medical waste management at Puskesmas Ponrang and Puskesmas Ponrang Selatan in Luwu Regency through naturalistic observation and in-depth interviews with the head of the Puskesmas, environmental health officers, and cleaning staff. The findings show that waste segregation between medical and non-medical waste has been implemented using yellow and black plastic bags, although standardized labeling and color coding are not fully applied. Waste is collected daily, but supporting facilities such as closed trolleys and temporary storage areas remain inadequate. In addition, transportation to third-party waste handlers is irregular, causing occasional waste accumulation, and the Puskesmas lack incinerators, making them dependent on external parties for final disposal. Overall, medical waste management in Luwu Regency’s Puskesmas has not fully complied with Ministry of Health Regulation No. 7 of 2019 and Ministry of Environment and Forestry Regulation No. P56 of 2015, indicating the need for improved facilities, enhanced staff training, and more integrated transportation and disposal systems to reduce health and environmental risks.